Formulasi Sediaan Lipbalm Ekstrak Bawang Tiwai (Eleutherine Americana Merr) Sebagai Pelembab Bibir: Lipbalm Formulation of Tiwai Onion Extract (Eleutherine Americana Merr) as Lip Moisturizer - Mutiara Citra Refordayanti; Novita Eka Kartab Putri; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Tiwai onion (Eleutherine Americana Merr) is a typical Kalimantan plant that is known to have various benefits. Local people use tiwai onions as a remedy for various types of diseases and plants which are provided as colorants in food or in cosmetic products because they have a red color caused by anthocyanin pigments. This study aims to make a lipbalm formulation from the extract (Eleutherine Americana Merr). The method used is experimental research methods. The test of the extract reaction was in the form of organoleptic, pH and solubility. The results obtained were the extract of tiwai onion extract in the form of organoleptic (color: brick red, thick extract, distinctive odor of tiwai onion), pH (5.86), solubility (soluble in ethanol, methanol and distilled water) which was in accordance with the parameters with Deng The results of the tiwai onion extract which can be formulated in lipbalm formulations (F1, F2, F3) have homogeneity in accordance with the parameters, the appropriate pH is F1 (5.79-6.20), F2 (5.87-6). , 21), and F3 (5,91-6,14) and for F1 organoleptics (color: milk orange, oleum rosae distinctive aroma, soft and smooth texture), F2 (color: light orange, oleum rosae distinctive aroma, soft texture and smooth, and F3 (color: orange, distinctive aroma of oleum rosae, soft and smooth texture). It can be neglected that tiwai onion extract can be formulated in lipbalm preparations.